1999
DOI: 10.1149/1.1390718
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Enhanced CO Tolerance in Proton Exchange Membrane Fuel Cells by Carbon Supported PtMo Alloy Catalyst

Abstract: We report a two-to threefold enhancement of CO tolerance in a proton exchange membrane (PEM) fuel cell, exhibited by carbon supported nanocrystalline PtMo/C as compared to the current state of the art PtRu/C electrocatalysts. The bulk of these nanocrystals were comprised of Pt alloyed with Mo in the ratio 8.7:1.3 as shown by both X-ray diffraction and in situ extended X-ray absorption fine structure measurements. Rotating disk electrode measurements and cyclic voltammetry in a PEM fuel cell indicate the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(64 citation statements)
references
References 18 publications
3
53
0
8
Order By: Relevance
“…Alloy catalysts help improve CO tolerance by altering the adsorption enthalpies of CO and H 2 , as well as their oxidation rates. Thus, a combination of increasing operating temperature of the PEMFC and modified electrocatalysts can reduce performance losses of a PEMFC in the presence of CO [23,24]. …”
Section: Co Tolerance and Operating Temperaturementioning
confidence: 99%
“…Alloy catalysts help improve CO tolerance by altering the adsorption enthalpies of CO and H 2 , as well as their oxidation rates. Thus, a combination of increasing operating temperature of the PEMFC and modified electrocatalysts can reduce performance losses of a PEMFC in the presence of CO [23,24]. …”
Section: Co Tolerance and Operating Temperaturementioning
confidence: 99%
“…This pseudocapacitive feature is attributed to the formation of OH species on Mo atoms on the surface of alloy particles. 23 The nature of the oxidation states of Mo surface atoms, however, is still obscure and not clearly resolved, but the investigation by Mukerjee and coworkers suggested that the oxyhydroxide state of Mo, predominantly as MoO(OH) 2 , is responsible for the oxidative removal of CO. 25 Another noticeable change in the cyclic voltammograms of Pt 4 Mo 1 /C catalysts is that the double-layer area becomes thicker as the annealing time increases. This implies that more Mo atoms were diffused out to the surface of alloy particles as the annealing under oxygen atmosphere was prolonged.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, spectroscopic analysis revealed that Mo surface atoms have active oxygen species at all potentials, which may act as a promoter for the oxidization of adsorbed CO on neighboring Pt atoms. 9,23,25 While the bifunctional mechanism sounds plausible as in the case of PtRu alloy catalyst, one cannot completely exclude another possible reason for the improved CO-tolerance: the adsorption strength of CO on Pt atoms. If CO molecules are less tightly bound to the surface of Pt, the removal of CO would be much easier and do not require high overpotentials for the oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A thin layer of Ru deposited on the surface of the electrode can act as a filter for CO thus improving tolerance of the fuel cell. Also, nanocrystalline PtMo/C catalysts have been reported to show a two to three times improvement in CO tolerance in a PEMFC as compared to the conventional Pt-Ru/C electrocatalysts [229].…”
Section: Electrode Catalystmentioning
confidence: 99%